Pain Catastrophizing and Its Association with Military Medical Disability Among US Active Duty Service Members with Chronic Predominately Musculoskeletal Pain: A Retrospective Cohort Analysis - Schaaf S; Flynn DM; Steffen AD; Ransom J; Doorenbos A (Journal of Pain Research, 2023)
Sherrill Schaaf,1,* Diane M Flynn,2,* Alana D Steffen,3 Jeffrey Ransom,2 Ardith Doorenbos3,4 1School of Health Sciences, A.T. Still University, Mesa, AZ, USA; 2Interdisciplinary Pain Management Center, Madigan Army Medical Center, Tacoma, WA, USA; 3College of Nursing, University of Illinois Chicago, Chicago, IL, USA; 4Department of Anesthesiology and Pain Medicine, University of Washington School of Medicine, Seattle, WA, USA*These authors contributed equally to this workCorrespondence: Diane M Flynn, Physical Performance Service Line, Madigan Army Medical Center, Tacoma, WA, 98431, USA, Tel +1-253-968-0618, Fax +1-253-968-0469, Email diane.m.flynn4.civ@health.milContext: Pain catastrophizing is characterized by negative emotional and cognitive responses to pain and is a predictor of work-related disability. Its association with military medical disability has not been studied.Objective: To (1) identify the pain catastrophizing scale (PCS) score cut point most strongly associated with military medical disability, (2) measure the difference in rate of disability between service members with baseline PCS scores above versus below the cut point, and (3) determine if improvement in PCS score during pain specialty care is associated with decreased likelihood of disability.Methods: This was a retrospective cohort analysis comparing PCS scores collected from US Army active duty service members at time of initial visit to an interdisciplinary pain management center and periodically during pain treatment. Outcome was determination during the following year of a military service-disqualifying disability.Results: Receiver operating characteristic (ROC) curves determined that a PCS score of 20 was the single cut point most closely associated with subsequent disability. Kaplan–Meier curves showed significantly higher disability rate during the following year among those with baseline PCS scores ≥ 20 (52%) compared to those with lower scores (26%). Scheffe-adjusted contrasts showed that service members with PCS scores ≥ 20 whose scores improved to < 20 at follow-up were significantly less likely to have a medical disability (42.6%; 95% CI, 0.07– 0.58) than those whose PCS score remained ≥ 20 (76.3%; 95% CI, 68.0%– 84.7%).Conclusion: A PCS score cut point of 20 distinguishes between high versus low likelihood of disability among service members. Those with high baseline PCS score had twice the likelihood of disability than those with low scores. Service members who decreased their PCS score from high to low during pain specialty care had lower likelihood of disability. Prospective research is needed to determine if treatments that lower pain catastrophizing yield reduced likelihood of subsequent disability.Plain Language Summary: Pain catastrophizing is a persistent tendency to have distressing thoughts and emotions related to pain and worsens work-related outcomes. This study examined the association between pain catastrophizing and military medical disability in a population of active duty US Army service members. The pain catastrophizing scale (PCS) scale is a 13-item questionnaire with a range of 0 (lowest catastrophizing) to 52 (highest catastrophizing). The aims of the study were to (1) identify the PCS score cut point most strongly associated with later military medical disability, (2) measure the difference in rate of disability between service members with baseline PCS scores above versus below the cut point, and (3) determine if improvement in PCS score during pain specialty care is associated with a decreased likelihood of disability. The study found that service members with high PCS scores were twice as likely to have medical disability than those with low scores. Additionally, those who reduced their PCS score were less likely to be medically disabled later. This study showed that PCS score may help to identify service members at increased risk of disability so that they may be offered therapies that reduce pain catastrophizing. The main limitation of this study is its retrospective design; we cannot be certain if improvement in PCS resulted in lower disability rates or if inherently more disabling conditions resulted in greater catastrophizing.Keywords: pain catastrophizing, chronic pain, interdisciplinary, disability, military